Our experience with surgery in situs inversus: Open peptic perforation repair and laparoscopic cholecystectomy in 1 patient and 3 patients respectively. (2016) - Ahmed, Zeeshan; Khan, Sami A.; Chhabra, Sanjeev; Yadav, Rahul; Kumar, Nitin; Vij, Vikesh; Saxena, Dhananjay; Talera, Devender; Kankaria, Jeevan; Gupta, Shalu; Bugalia, Rajendra P.; Goyal, Amit; et al.
Highlights: Surgical diagnosis of conditions causing acute abdominal pain in situs inversus is complicated by the mirror image anatomy. Chest X-ray and Ultrasonography abdomen can be helpful in diagnosing this condition. Laparoscopic cholecystectomy in situs inversus is problematic for right handed surgeons. We describe a modified 4 port configuration where right handed surgeons can use the left mid-clavicular port for dissection. Abstract: Introduction: Situs inversus is a rare autosomal recessive condition associated with complete transposition of abdominal +/− thoracic organs. Surgical diagnosis and surgical procedures in patients with situs inversus is tricky because of the mirror image anatomy of intra-abdominal organs. Materials and methods: A retrospective analysis of 2152 and 1497 patients who underwent laparoscopic cholecystectomy and open peptic perforation repair respectively from June 2014-June 2016 was done. 1 patient and 3 patients with situs inversus underwent open peptic perforation repair and laparoscopic cholecystectomy respectively. A 10 mm left para-median port 5 cm caudally from xiphoid was used for grasping the infundibulum. Two 5 mm ports placed 10 cm caudally from costal margin in the mid-clavicular and anterior axillary line were used for dissecting and retracting fundus respectively. A 10 mm supra-umbilical camera port was used. Results: A 40 year male with situs inversus totalis underwent open peptic perforation repair. Laparoscopic cholecystectomy was done in 3 female patients with situs inversus aged 33–46 year (mean 41 year). Mean operative time for laparoscopic cholecystectomy was 59 min (39–93). There were no intraoperative or post-operative complications. Histopathology revealed chronic inflammation in peptic perforation and cholecystitis. Conclusion: Perforation peritonitis in situs inversus can cause diagnostic confusion with free gas under the left hemi diaphragm. Laparoscopic cholecystectomy in situs inversus is ergonomically inconvenient and technically difficult for right handed surgeons. We describe an ergonomically convenient port placement for right handed surgeons in situs inversus.